Analisis Hukum Perundang-Undangan Tentang Lembaga Pemasyarakatan Dalam Perspektif Sistem Pembinaan, Hak Narapidana, Dan Budaya Hukum - Muhammad Orie Anantama; Fariz Jundan; Agus Satory (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The correctional system in Indonesia is a manifestation of a paradigm shift from a prison system that emphasizes punishment to one that focuses on rehabilitation oriented toward the moral and social recovery of prisoners. Prisons serve as a means of rehabilitation so that prisoners can once again play a positive role in society. This study discusses three main issues, namely the legal basis governing the correctional system, the application of prisoners' rights and obligations, and the role of legal culture in shaping law-abiding behavior. The research method used is normative juridical with a legislative and conceptual approach. The results of the study show that the success of guidance in prisons is greatly influenced by the consistent implementation of legal norms, the professionalism of officers, and the internalization of legal values in prisoners. It is necessary to strengthen regulations, improve the quality of officers, and provide guidance based on humanity in order to realize an effective and fair correctional system.